2016
DOI: 10.4172/2155-6156.1000654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Pharmacist’s Delivered Counseling on Medication Adherence and Glycemic Control in Patients with Diabetes Mellitus

Abstract: Introduction: Diabetes mellitus is a metabolic disorder leading to significant morbidity and mortality and negatively affects patient quality of life. Lifestyle modifications and patient medication adherence are the most important factor that contributes to effective management. Objectives:To assess the impact of pharmacist delivered counseling on medication adherence and glycemic control in patients with diabetes mellitus. Method:It was a prospective, interventional study carried over a period of 12 months fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…These findings are nearly similar to the results of a diabetic study conducted by Shareef et al . [17] Other outcomes such as SBP and LDL-cholesterol are also significantly reduced in the intervention group compared to usual care with a P < 0.01. These findings are consistent with the results of the study conducted by Shao et al .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are nearly similar to the results of a diabetic study conducted by Shareef et al . [17] Other outcomes such as SBP and LDL-cholesterol are also significantly reduced in the intervention group compared to usual care with a P < 0.01. These findings are consistent with the results of the study conducted by Shao et al .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the measurement results, the poor adherence decreased from 48.2% to 26.1%, moderate adherence increased from 32.1% to 39.1% and high adherence increased from 19.7% to 34.9% with significance value of P = 0.000 (<0.05) which indicates that the treatment adherence of DM patients increased significantly after pharmacist intervention 31 . Research conducted by Shareef and Fernandes 32 , and Butt et al, 33 , also showed similar results, in which pharmacist intervention through education, counseling, and monitoring related to disease and DM therapy possess a significant effect in improving treatment adherence to DM patients. Various studies related to the intervention conducted by pharmacists show a good effect on patient 2 , also shows that in addition to providing education and counseling, PMR, MAP, the diabetes calendars and/or leaflets provided as part of the MTM service program are effective in increasing the adherence of patient treatment.…”
Section: Patients Characteristicsmentioning
confidence: 56%
“…It is, however, well documented that community pharmacy service programmes supporting adherence have a significant effect on glycaemic control, improve medication adherence and improve blood pressure. 19 , 55 , 56 Interventions by community pharmacies may therefore to a greater extent help persons with diabetes to self-manage their medication and life with diabetes. 57 However, community pharmacy services are not connected with the rest of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%